How to deal with the Black Sheep? An evaluation of journalists’ reactions towards intentional selfscandalization by politicians - Haller, André (Journal of Applied Journalism & Media Studies, 2015)
Abstract Under normal circumstances scandals are negative events for the scandalized persons or institutions. The communication of transgressions of norms or values, followed by public outrage is the beginning of a scandal. Media plays the most important role in what science calls ‘media scandal’, ‘mediated scandal’ or ‘mediatized scandal’. The scandalized players have to react to the accusations; therefore they have to use the media to reach a broad public. Journalists have the power to control which players have the right to speak and how the scandal is communicated to the public. This article will show a new form of scandal, the so called intentional self-scandalization.1 That type of scandal, which will be shown in the field of political communication, is produced on purpose by the scandalized politicians to achieve certain communicative goals. The theory will then be demonstrated using a concrete example, the scandal of a racial campaign in Switzerland in the year 2007. The article identifies three possible reactions by journalists to this special form of scandal: Scandalizing the intended transgression, ignoring it or thematizing the strategy of the scandalized player. The text will also analyse the advantages and disadvantages of the patterns.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9ham1zLjQuMy40MzVfMQ